The role of anatomy demonstrators: A surgical trainees' perspective. Issue 3 (28th November 2017) - Smith, C.F.; Gami, B.; Standfield, N.; Davies, D.C.
Abstract : Core Surgical Trainees (CST) in the London (UK) Postgraduate School of Surgery receive clinical anatomy teaching in their first year of training, and, in their second year, give 30 sessions of anatomy teaching to medical and other students. This study set out to investigate the role of demonstrators from the perspective of the trainees. A focus group was convened to ascertain trainees' perspectives on demonstrating anatomy and to identify problems and improvement strategies to optimize their ability to enhance students' learning. A questionnaire was formulated and all second‐year CST ( n = 186—from two cohorts) in the London Postgraduate School of Surgery were invited. A total of 109 out of 186 trainees completed the questionnaire. A high percentage (98%) of trainees that completed the questionnaire responded that demonstrating was an invaluable part of their training. Sixty‐two per cent responded that anatomy teaching they received in their first year of core surgical training helped them in their teaching role and 80% responded that it helped them prepare for surgical training. The study also revealed the need for improved communication between trainees and the London Postgraduate School of Surgery/Medical Schools/National Health Service Trusts to address issues such as trainees' perceived difficulty in fulfilling their teaching session requirement. The stakeholders have acknowledged and addressed the outcomes to improve the experience for both surgical trainees and students. The results indicate that anatomy demonstrating delivers important benefits to early surgical trainees, in addition to those received by the students that they teach. Clin. Anat. 31:409–416, 2018. © 2017 Wiley Periodicals, Inc.